Offenses Affecting Public Safety, Ordinances of the City Council of Memphis, Ch.14, Art. 3, §1 (1867). - (:unkn) unknown (My University, 1867)
Regulated the manufacture, transportation and storage of gunpowder
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER